2020
DOI: 10.1088/1757-899x/736/6/062014
|View full text |Cite
|
Sign up to set email alerts
|

Application of anthocyanin natural colors from Butterfly Pea (Clitoria ternatea L.) extracts to cupcake

Abstract: In this study, we compared the content of nutritional indicators including lipid, moisture, pH, protein, and ash between original and Butterfly Pea cupcake baked at 170°C for 20 minutes. Moreover, the sensory properties of Butterfly Pea cupcake favorite also are determined. There was an increase in the content of moisture, protein compared with those of the control cupcake, reaching 22.12 ± 1.87 and 3.69 ± 0.51, respectively. In contrast, the level of pH, ash, and lipid witnessed marginal decreases, reaching 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Eliasova et al (2020) reported that the most abundant anthocyanins of blue grain wheat were delphinidin‐3‐rutinoside, and that 45–51% of anthocyanins were lost in baking stage of blue‐grain wheat bread. Thanh et al (2020) found that only 41.8% of the initial anthocyanin content was retained in the cupcake with the anthocyanin extract of CT flower after baking at 170°C for 20 min. Sui et al (2015) reported that the degradation rate (k ref ) of cyanidin‐3‐glucoside and cyanidin‐3‐rutinoside in black rice‐incorporated bread crumbs at reference temperature of 65°C was 2.49 × 10 −5 and 1.93 × 10 −5 (s −1 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eliasova et al (2020) reported that the most abundant anthocyanins of blue grain wheat were delphinidin‐3‐rutinoside, and that 45–51% of anthocyanins were lost in baking stage of blue‐grain wheat bread. Thanh et al (2020) found that only 41.8% of the initial anthocyanin content was retained in the cupcake with the anthocyanin extract of CT flower after baking at 170°C for 20 min. Sui et al (2015) reported that the degradation rate (k ref ) of cyanidin‐3‐glucoside and cyanidin‐3‐rutinoside in black rice‐incorporated bread crumbs at reference temperature of 65°C was 2.49 × 10 −5 and 1.93 × 10 −5 (s −1 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we suggest that anthocyanin‐rich colorful CSB can be prepared with 20–30% BPFE in order to increase the intake of bioactive substances and maintain consumers' sensory acceptability. Thanh et al (2020) reported that cupcakes with CT flower anthocyanins extract had higher aroma, color, flavor and overall acceptability than the control samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies evidently showed that the antioxidant activity of food increases when anthocyanins from blue pea flowers are used as a food colourant. Thanh et al (2020) investigated the application of blue pea flower anthocyanin extract in cupcakes. After baking at 170 • C for 20 min, only 41.8% of the initial anthocyanin content was retained in the cupcake.…”
Section: Applications Of Anthocyanins From Blue Pea Flowermentioning
confidence: 99%
“…Anthocyanins have been shown to give benefits in visual acuity, cancer, heart disease and age-related neurodegenerative disorders (Ray et al, 2009). Besides, the epidemiologic studies suggested the anti-oxidant, anti-microbial and anti-inflammatory activities of anthocyanins can lower the risk of cardiovascular disease, diabetes, arthritis and cancer (Prior and Wu, 2006;Thanh et al, 2020). Hwang et al (2011) reported that anthocyanins can boost memory and the anti-carcinogen activities of the anthocyanins are competent to protect the liver.…”
Section: Introductionmentioning
confidence: 99%